Adaptation to the undergrowth of a community of Andean palms (Arecaceae) from the vital rates perspective: The adaptation to the understory of a community of Andean palms seen from the vital rates perspective - Cepeda, Paula; Jiménez, Pedro; Isaza, Carolina (Revista de Biología Tropical, 2022)
Introduction: Palms have adaptations to thrive in the limiting environment of the understory, which can be examined from studying their survival, growth and fecundity rates. However, studies that address the vital rates strategies developed by a community of palms to successfully inhabit the forest understory are scarce. Objective: To determine and compare the vital rates of survival, growth and fecundity in a community of Andean understory palms. Methods: The study was carried out in the Chicaque Natural Park, Colombia in an area occupying 0.07 ha, focused on the species Chamaedorea linearis, C. pinnatifrons, Geonoma orbignyana and G. undata. During 2018 and 2019, data corresponding to survival, growth and fecundity of these species were collected. The vital rates were estimated from their relationship with the size of the individuals. Results: A total of 597, 687, 453 and 690 individuals were registered in 0.1 ha of C. linearis, C. pinnatifrons, G. orbignyana and G. undata, respectively. The four species had high survival of seedlings, low growth rates in stemless individuals, low leaf production, few total leaves, a high longevity of the leaves and start of reproduction with low-height aerial stem. However, we found differences among species in which G. orbignyana and C. pinnatifrons demonstrated patterns commonly seen in understory palms. By contrast, C. linearis and G. undata had mixed growth strategies to cope with open spaces and understory conditions, as their leaves are larger, have larger stem growth rates and reproduction begins at a higher height. In terms of the genera, Chamaedoreas had fast growth and reproduction rates, spending most of their lives as adults. Meanwhile, Geonomas prioritizes the stasis of individuals, with its long-life cycles and lower growth rates. Conclusions: Chamaedoreas prioritizes growth and reproduction, while Geonomas prioritizes stasis. The limiting conditions of the understory seem to favor these two growth strategies in the species. These results can be considered as a step towards better understanding the strategies of a community of palms in the understory.